Optimization and Antioxidant Activity of Flavonoids Extract from Diospyros kaki Thunb. 'Mopan' Pulp - Duan, Rong; Zhao, Zhihui; Zhang, Yuxing; Liu, Mengjun; Wang, Wenjiang (Asian Journal of Chemistry, 2013)
The ultrasonic-assisted extraction technique for flavonoids from ‘Mopan’ persimmon pulp was studied and the optimization of technological parameters were obtained by response surface methodology (RSM) with flavonoids extraction rate as index and the antioxidant activities of the extracts were determined. The optimal extraction conditions were using 70 % ethanol as solvent, ratio of liquid to solid 50:1, extraction time of 50 min, ultrasonic power of 450 W and obtained the extraction rate of 1.57 %. The results showed good fits with the proposed model for flavonoids extraction rate (R2 = 0.95). The flavonoids extract prepared by the optimal condition from ‘Mopan’ persimmon pulp showed high antioxidant activity and a high correlation was obtained between the flavonoids content and the antioxidant activity of ‘Mopan’ persimmon.